Penerapan Model Pembelajaran Word Square Untuk Meningkatkan Minat Belajar IPAS Siswa Kelas V SD Inpres 6/75 Corawali Kecamatan Barebbo Kabupaten Bone - Sitti Jauhar; Satriani DH; Azizah, Ulfiyah (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
This research is a classroom action research aimed at increasing the interest in learning IPAS among fifth-grade students of SD Inpres 6/75 Corawali, Barebbo District, Bone Regency, through the Word Square learning model. The data collection techniques used were observation and questionnaires. The data analysis techniques used in this research are data reduction, data presentation, and drawing conclusions. The research results show that the Word Square learning model can increase the interest in learning IPAS among fifth-grade students at SD Inpres 6/75 Corawali, Barebbo District, Bone Regency. This can be proven by the students' learning interest in cycle I, where 12 out of 20 students achieved the success indicator with a percentage of 60% (Sufficient), whereas in cycle II, 18 out of 20 students achieved the success indicator with a percentage of 90% (Good). The percentage of teacher activity in cycle I reached 73.33% (Satisfactory), while the percentage in cycle II reached 86.67% (Good). The percentage of student activity in cycle I reached 66.67% (Satisfactory), while the percentage in cycle II reached 80% (Good). It can be concluded that the Word Square Learning Model can increase students' interest in learning